2017
DOI: 10.1007/s12550-017-0300-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of enzyme-linked immunosorbent assay to screen for aflatoxins, ochratoxin A, and deoxynivalenol in dry pet foods

Abstract: The objective of this study was to perform a market survey on dry pet foods using enzyme-linked immunosorbent assay (ELISA) to detect total aflatoxins (AFs), ochratoxin A (OTA), and deoxynivalenol (DON). Pet food products (n = 58) marketed for dogs, cats, birds, and rabbits were tested in duplicate with ELISA, and results above the limit of quantitation were confirmed using liquid chromatography tandem mass spectrometry (LC-MS/MS). OTA was detected in one product (rabbit food) and AFs were detected in two prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…The problem may be chronic exposure to mycotoxins and their modified forms. The results of the research by Okuma et al [107] revealed a low prevalence of AF and OTA in commercial pet foods. Although DON has been detected in many trials, its levels were well below those likely to cause acute toxic effects.…”
Section: Pet Food and Feedmentioning
confidence: 95%
“…The problem may be chronic exposure to mycotoxins and their modified forms. The results of the research by Okuma et al [107] revealed a low prevalence of AF and OTA in commercial pet foods. Although DON has been detected in many trials, its levels were well below those likely to cause acute toxic effects.…”
Section: Pet Food and Feedmentioning
confidence: 95%
“…One disadvantage of ELISAs is susceptibility to matrix effects, causing the reported analyte level to be falsely elevated or depressed. We used an ELISA method designed to be resistant to matrix interferences and which was previously validated to test disparate sample types, such as pet food [44], sorghum [45], maize [46], nuts, spices and many others [47]. Lack of requirement for sample clean-up and specialized equipment, skilled personnel for quantification by ELISA together with improved upstream sample handling procedures described herein, combined with high throughput (42 samples per run), guarantee rapid and reliable estimation of aflatoxin in complex and amorphous matrices such as animal feed.…”
Section: Enzyme-linked Immunosorbent Assay Of Prepared Standards For Determination Of Aflatoxin Content In Chicken Feed Samplesmentioning
confidence: 99%
“…Consequently, food safety testing is necessary, usually achieved using chromatography, spectroscopy‐based technologies, and biotechnologies. Chromatography includes gas chromatography (Giri et al., 2015; Huertas‐Pérez et al., 2018; Omeje et al., 2021), high‐performance liquid chromatography (Esteki et al., 2019; Guo et al., 2020; Zhao et al., 2022), thin‐layer chromatography, and immunoaffinity chromatography (Carvalho et al., 2012; Castegnaro et al., 2006; Santos & Vargas, 2002); spectroscopy‐based technologies include Raman spectroscopy (Kashif et al., 2021; Li & Church, 2014; Neng et al., 2020; Nilghaz et al., 2022), infrared spectroscopy (Jiménez‐Carvelo et al., 2021; Levasseur‐Garcia, 2018; Qu et al., 2015), fluorescence spectroscopy (Ahmad et al., 2017; Bartolic et al., 2022; Fan & Su, 2022); biotechnologies including enzyme‐linked immunosorbent assay (Lin et al., 2021; Okuma et al., 2018; Zhu et al., 2022), PCR technology (Hunt et al., 2018), and biochips. However, the development of the abovementioned food safety testing technologies is largely limited by the dependence on complicated pretreatment of samples, a low limit of detection (LOD), large errors in testing results due to insensitivity to reactions, and a relatively long reaction period.…”
Section: Introductionmentioning
confidence: 99%